The Boulder and the Sphere: Subjectivity and Implicit Values in Biology. (1st February 1995) - Alpert, Peter
Abstract : Science is inherently subjective. The experience of dissertation research in ecology showed how intuitively derived hypotheses and assumptions define the questions one asks and the variables one measures, and how idealised forms and generalised types facilitate analysis but distort interpretation. Because these conceptual tools are indispensable to science, subjectivity is ineluctable. This has moral implications. Scientists are responsible for the particular abstractions they select and must therefore accept some moral responsibility for the way their results are used. Those who use scientific results have an equal responsibility to acknowledge the significance of the methods and not just of the conclusions. In biology, subjectivity may also have a positive side. A wide consensus of ecological biologists accept, on the apparently neutral grounds of accumulated study, a set of generalisations that society at large treats more as philosophical beliefs. This category of implicit values in biology holds much promise for improving our relations with nature and each other.